Symmetry Criterion for Patients with Rheumatoid Arthritis of the Foot: A Cross-Sectional Study. - Sánchez-Castillo, José Alberto; Reinoso-Cobo, Andrés; Gijón-Noguerón, Gabriel; Cáliz Cáliz, Rafael Antonio; Exposito-Ruiz, Manuela; Ramos-Petersen, Laura; Ortega-Ávila, Ana Belén (MDPI, 2021)
Objective: The aim of the study was to analyze the feet of rheumatoid arthritis (RA) patients, to determine the degree to which both feet were affected, primarily analyzing the severity of RA in both feet looking at structure and morphology, and secondly looking at the symmetry in terms of the anthropometrics and posture. Method: This cross-sectional study was conducted from January to December 2018. The data from 229 patients with RA and with foot pain and no RA recruited (Granada, Spain) were analyzed. Two researchers independently interviewed the patients to obtain the study data. The clinical data were obtained using specific foot health and quality of life questionnaires and a validated platform for foot measurement. Anthropometric measurements were obtained by means of a foot measurement platform and the Foot Posture Index (FPI). The bivariate analysis was performed with the Student's t test and the non-parametric Wilcoxon test. The level of significance was established at p < 0.05. Results: In the RA group, anthropometric measurements revealed significant differences between the left and right feet in 13 of the 23 parameters considered, as follows: (non-load-bearing) foot length, length of the first metatarsophalangeal joint, maximum height of the internal longitudinal arch, and width of the midfoot (p < 0.001, p = 0.038, p < 0.001, and p = 0.037 respectively); and Foot Posture Index (p = 0.001). Conclusions: In patients with RA, statistically significant differences were found in the Foot Posture Index and in several parameters related to foot structure and morphology. From this, we conclude that from a morphological, structural, and postural standpoint, a pattern of symmetric joint involvement should not be viewed as a specific criterion for RA in the foot.
Keywords: Artritis reumatoide; Pies - Enfermedades - Tratamiento; Symmetry; Foot health; Functionality; Pain; Rheumatoid arthritis